2004
DOI: 10.1002/ajim.20020
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tobacco dependence treatment in the context of a “smoke‐free grounds” worksite policy: A case study

Abstract: A "smoke-free grounds" policy encourages abstinence and may play a significant role in harm reduction among continuing tobacco users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Following the extension of a smoke-free indoor policy to include outdoor spaces at 1 worksite, participants who enrolled in smoking cessation programs had higher 6-month quit rates after the extension (52.4%) than before (43.0%); post-ban participants were 80% less likely to relapse than pre-ban participants, and nonquitters decreased their consumption by 6.6 cigarettes per day, a 39% decrease. 442 …”
Section: Resultsmentioning
confidence: 99%
“…Following the extension of a smoke-free indoor policy to include outdoor spaces at 1 worksite, participants who enrolled in smoking cessation programs had higher 6-month quit rates after the extension (52.4%) than before (43.0%); post-ban participants were 80% less likely to relapse than pre-ban participants, and nonquitters decreased their consumption by 6.6 cigarettes per day, a 39% decrease. 442 …”
Section: Resultsmentioning
confidence: 99%
“…Smoke-free policies in campuses certainly reduces exposure to tobacco smoke, increases quit rates, prevents initiation of smoking among youths and also reduces daily cigarette consumption among habitual smokers. [910] It might also change the behavior of the health-care professionals and patients towards smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Research on adoption of 100% smoke-free campus wide policies in schools and workplaces has shown that, if enforced, these policies decrease tobacco consumption [7,8]. While research documenting the successes or effectiveness of SFHC or TFHC policies on employees, patients, or visitors to U.S. hospitals is quite limited, the potential positive health effects are substantial [9].…”
Section: Resultsmentioning
confidence: 99%